1998
DOI: 10.1073/pnas.95.16.9572
|View full text |Cite
|
Sign up to set email alerts
|

The hereditary renal cell carcinoma 3;8 translocation fuses FHIT to a patched- related gene, TRC8

Abstract: The 3;8 chromosomal translocation, t(3;8)(p14.2;q24.1), was described in a family with classical features of hereditary renal cell carcinoma. Previous studies demonstrated that the 3p14.2 breakpoint interrupts the fragile histidine triad gene (FHIT) in its 5' noncoding region. However, evidence that FHIT is causally related to renal or other malignancies is controversial. We now show that the 8q24.1 breakpoint region encodes a 664-aa multiple membrane spanning protein, TRC8, with similarity to the hereditary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
114
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 48 publications
4
114
0
5
Order By: Relevance
“…Similar ®ndings were obtained using anti-HA antibodies or an a nity puri®ed polyclonal rabbit antiserum speci®c for hTRC8 (not shown). However, we were unable to detect endogenous TRC8 proteins by immuno¯uores-cence or Western blots despite ubiquitous mRNA in human (Gemmill et al, 1998) and Drosophila. Using a heat-shock inducible myc-tagged DTrc8 transgene in Drosophila embryos, DTrc8 was observed to disappear from Western blots after 15 min of recovery (not shown).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar ®ndings were obtained using anti-HA antibodies or an a nity puri®ed polyclonal rabbit antiserum speci®c for hTRC8 (not shown). However, we were unable to detect endogenous TRC8 proteins by immuno¯uores-cence or Western blots despite ubiquitous mRNA in human (Gemmill et al, 1998) and Drosophila. Using a heat-shock inducible myc-tagged DTrc8 transgene in Drosophila embryos, DTrc8 was observed to disappear from Western blots after 15 min of recovery (not shown).…”
Section: Introductionmentioning
confidence: 93%
“…In addition, some t(3;8) carriers developed non-medullary thyroid cancer (Li et al, 1993), not a recognized feature of the VHL syndrome ). The t(3;8) breakpoint generates a fusion transcript involving the 5' untranslated portion of FHIT and the coding region of a novel gene, TRC8 (Gemmill et al, 1998). TRC8 encodes a multi-membrane spanning protein with partial similarity to the Hedgehog receptor, Patched (Hahn et al, 1996;Johnson et al, 1996;Gailani et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…(9,10) PTCH1 is composed of N-and C-terminal domains, two large extracellular and one large intracellular loops, and 12-pass transmembrane domains, two to six of which form the putative sterol-sensing domain (SSD) considered to participate in vesicular trafficking of cholesterol and other lipids. (11,12) We and other groups have reported that more than 85% of patients with NBCCS harbor heterozygous germline PTCH1 mutations, (13)(14)(15) primarily consisting of PTCH1 protein truncations (73%) that are usually concentrated in the large extracellular and intracellular loops and in the N-terminal region. Germline missense mutations (17%) occur primarily in the transmembrane domains and especially in the SSDs.…”
Section: Introductionmentioning
confidence: 99%
“…TRC8 is a multimembrane spanning ER-resident protein containing a RING-H2 finger with demonstrable E3-ubiquitin ligase activity (Lorick et al, 1999;Gemmill et al, 2002). In addition, it has partial similarity to the Hedgehog receptor, Patched (Gemmill et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…While most familial RCC cases are caused by mutations in the VHL (von Hippel-Lindau) gene, affected individuals in this family lacked germline VHL mutations and other manifestations of VHL syndrome. The (3;8) rearrangement fuses 5 0 -untranslated FHIT sequences with the C-terminal coding portion of TRC8 (translocation in renal cancer from chromosome 8), interrupting a predicted sterolsensing domain (Gemmill et al, 1998). TRC8 is a multimembrane spanning ER-resident protein containing a RING-H2 finger with demonstrable E3-ubiquitin ligase activity (Lorick et al, 1999;Gemmill et al, 2002).…”
Section: Introductionmentioning
confidence: 99%